Subgeneric classification of the Palaearctic bees of the genus Evylaeus Robertson (Hymenoptera: Halictidae) - Pesenko, Yuri A. (Zootaxa, 2007)
A subgeneric classification for the 318 currently recognised species of the genus Evylaeus recorded from the Palaearctic Region (in the narrower understanding) is suggested. It includes 29 subgenera all of which are keyed. An annotated list of subgenera contains diagnoses and information about type species, general geographic distribution, and species included. The following 19 new subgenera are described: Aerathalictus subg. n. (type species: Melitta aerata Kirby), Biennilaeus subg. n. (type species: Halictus marginatus Brullé), Crassevylaeus subg. n. (type species: Halictus crassepunctatus Blüthgen), Fratevylaeus subg. n. (type species: Halictus fratellus Pérez), Glauchalictus subg. n. (type species: Halictus problematicus Blüthgen), Laevinodilaeus subg. n. (type species: Halictus laevinodis Morawitz), Limbevylaeus subg. n. (type species: Halictus limbellus Morawitz), Loethalictus subg. n. (type species: Halictus loetus Brullé), Malachevylaeus subg. n. (type species: Melitta malachura Kirby), Minutulaeus subg. n. (type species: Hylaeus minutulus Schenck), Monilevylaeus subg. n. (type species: Halictus immunitus Vachal), Nitidiusculaeus subg. n. (type species: Melitta nitidiuscula Kirby), Nodicornevylaeus subg. n. (type species: Halictus nodicornis Morawitz), Pallidevylaeus subg. n. (type species: Nomioides pallida Radoszkowski), Pauxevylaeus subg. n. (type species: Hylaeus pauxillus Schenck), Tricinctevylaeus subg. n. (type species: Halictus tricinctus Schenck), Truncevylaeus subg. n. (type species: Halictus truncaticollis Morawitz), Virenshalictus subg. n. (type species: Hylaeus virens Erichson), Viridihalictus subg. n. (type species: Halictus viridis Brullé). Hylaeus politus Schenck is fixed as the type species of the subgenus Pyghalictus Warncke 1975. Evylaeus albitarsoides (Blüthgen) is resurrected as a valid species. The following new synonymies are ascertained: Halictus fedtschenkoi Blüthgen 1938 = Lasioglossum andromeda Ebmer 1978, syn. n.; Lasioglossum fratellus betulae Ebmer 1978 = L. nupricola Sakagami 1988, syn. n. The lectotype of Halictus fedtschenkoi Blüthgen is designated. Advantages of a more finely divided and hierarchically deeper classification of large taxa are discussed. A synonymic catalogue of species-group names of the Palaearctic Evylaeus, comprising 679 names, appended.